THE CORRELATION BETWEEN LEARNING MOTIVATION, PEERS, AND INTENSITY OF LEARNING WITH MATHEMATICS LEARNING OUTCOMES OF GRADE X STUDENTS OF SMA NEGERI 1 TURI - Mifathul Jannah; Widayati Widayati (Universitas Ahmad Dahlan, 2017)
Based on the information from SMA Negeri 1 Turi, student motivation in learning is still lacking, there are students who spoke with the classmate during the teaching and learning activities, as well as some students learning intensity is low. This study aims to determine whether there is a positive and significant relationship between motivation to learn, peers and learning intensity with mathematics learning outcomes in class X SMA Negeri 1 Turi Odd Semester of the school year 2016/2017. The study population was all students in grade X SMAN 1 Turi MIPA odd semester of the school year 2016/2017. The study was taking theÂ X MIPA 2 class as the research sample by random sampling technique toward the class. Data collection techniques in the form of technique tests and questionnaires. The research instrument test was using validity testing, different power testing, and reliability testing. Prasyarat test analysis included a normality test, independent test, linearity test. Analysis of the data for testing hypotheses was using correlation analysis and linear regression analysis. The results showed that there was a positive and significant correlation between motivation to learn, peers and intensity of learning with learning outcomes mathematics, with Â , and the linear regression equation . The donations were measured relatively X1 = , X2 = , X3 = Â and also effective contribution X1 = , X2 = , X3 = . This indicates that the peers (X2) have a greater relationship with mathematics learning outcomes compared to the study motivation (X1) with mathematics learning outcomes and learning intensity (X3) with mathematics learning outcomes.